Role of wide-field autofluorescence imaging and scanning laser ophthalmoscopy in differentiation of choroidal pigmented lesions - Reznicek, Lukas (International Journal of Ophthalmology Press, 2014)
AIM: To evaluate the diagnostic properties of wide-field fundus autofluorescence (FAF) scanning laser ophthalmoscope (SLO) imaging for differentiating choroidal pigmented lesions. METHODS: A consecutive series of 139 patients were included, 101 had established choroidal melanoma with 13 untreated lesions and 98 treated with radiotherapy. Thirty-eight had choroidal nevi. All patients underwent a full ophthalmological examination, undilated wide-field imaging, FAF and standardized US examination. FAF images and imaging characteristics from SLO were correlated with the structural findings in the two patient groups. RESULTS: Mean FAF intensity of melanomas was significantly lower than the FAF of choroidal nevi. Only 1 out of 38 included eyes with nevi touched the optic disc compared to 31 out of 101 eyes with melanomas. In 18 out of 101 melanomas subretinal fluid was seen at the pigmented lesion compared to none seen in eyes with confirmed choroidal nevi. In “green laser separation”, a trend towards more mixed FAF appearance of melanomas compared to nevi was observed. The mean maximal and minimal transverse and longitudinal diameters of melanomas were significantly higher than those of nevi. CONCLUSION: Wide-field SLO and FAF imaging may be an appropriate non-invasive diagnostic screening tool to differentiate benign from malign pigmented choroidal lesions.